SOCIAL CRITICISM IN THE POEMS AND DRAMAS CREATED BY W.S. RENDRA FROM NINETEEN SEVENTIES TO NINETEEN NINETIES - Sudewa, I Ketut; Darma Putra, I Nyoman; Kutha Ratna, I Nyoman (e-Journal of Linguistics, 2013)
This study analyzed the poems and dramas created by W.S. Rendra which were published from nineteen seventies to nineteen nineties. Such an era was a period of time during which Rendra creatively created his literary works. Politically, the decade from nineteen seventies to nineteen nineties was an era during which the Authoritative New Order held the power and did not hesitate to take action against those, including artists, who bravely expressed their criticisms. It was in that repressive period of time that Rendra appeared as a poet who so bravely used the poems and dramas he created to articularize his social criticisms. This study aims at revealing the themes and consistency of the social criticisms expressed by Rendra in the poems and dramas he created. This study was importantly conducted as the social criticisms the literary works Rendra created were not only strong but are still currently factual as well.  Many researchers have analyzed the social criticisms the poems and dramas created by Rendra contained but none had analyzed such a topic comprehensively and consistently. This present study attempted to complete the studies previously conducted so that the ideas, thoughts and concepts expressed by him through his literary works can be more comprehensively understood and exceed the era when they were created. The theory of sociology of literature and the theory of semiotics were used to analyze the social criticisms expressed by Rendra through his literary works. The theory of literature was used to analyze the social criticisms by contextualizing the themes and era when he created his poems and dramas, and the theory of semiotics was used to analyze the meanings of the sign systems the two genres contained. These two theories were used at the same time and were supported by the other relevant theories such as the theory of politics, the theory of capitalism, and the theory of feminism. His dramas were analyzed before his poems so that the consistency of the social criticisms he expressed in the two genres could be described. The result showed that the social criticisms expressed by Rendra in his poems included four great themes; they were values of feminism, education, capitalism and poverty, politics and law. His dramas also contained such social criticisms, as exemplified by the poems “Sajak Sebotol Bir” and “Sajak Pulau Bali” and the drama “Kisah Perjuangan Naga”, which contained the theme of how vicious capitalism was. The language styles used to articulate his social criticisms were also identical, indicated by the use of metaphors, repetitions, paradoxes, rhetorical questions, ironies, and cynicisms.  His consistency in expressing social criticisms through his poems and dramas made him successful in becoming the most talkative man of letters during the Indonesia’s history of literature.
Keywords: social criticism, poem, drama, consistency